2015
DOI: 10.1089/scd.2014.0096
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Neural Stem Cells Clonally Derived from Embryonic Stem Cells Promotes Recovery After Murine Spinal Cord Injury

Abstract: The pathology of spinal cord injury (SCI) makes it appropriate for cell-based therapies. Treatments using neural stem cells (NSCs) in animal models of SCI have shown positive outcomes, although uncertainty remains regarding the optimal cell source. Pluripotent cell sources such as embryonic stem cells (ESCs) provide a limitless supply of therapeutic cells. NSCs derived using embryoid bodies (EB) from ESCs have shown tumorigenic potential. Clonal neurosphere generation is an alternative method to generate safer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 65 publications
4
71
2
Order By: Relevance
“…Transplantation of NS/PCs is promising treatment for SCI. [99][100][101][102][103] NS/PCs usual has been studied as a mean to replace the damaged neurons in SCI. However, increasing data showed that NSCs can promote motor functional recovery by modulating the host environment.…”
Section: Ns/pcs and Macrophage Polarizationmentioning
confidence: 99%
“…Transplantation of NS/PCs is promising treatment for SCI. [99][100][101][102][103] NS/PCs usual has been studied as a mean to replace the damaged neurons in SCI. However, increasing data showed that NSCs can promote motor functional recovery by modulating the host environment.…”
Section: Ns/pcs and Macrophage Polarizationmentioning
confidence: 99%
“…Clip-compression spinal cord injuries at the T6 level in mice were performed similarly to previously described techniques [19]. In brief, a T5-T7 laminectomy was performed, allowing for the passage of a modified aneurysm clip (FEJOTA mouse clip) at T6.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…The NSC transplantations were performed as previously described [19]. Immune suppression using cyclosporine A (20 mg/kg) began 2 days before transplantation and continued for the duration of the experiment.…”
Section: Intraspinal Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the use of NSCs clonally derived from ESCs for spinal cord injury repair provide much better results than does traditional ESC transplantation. However, current studies have indicated that the prospect of clinical application of ESCs is not optimistic because of the following reasons: 1) the research subjects for spinal cord injury repair using ESC transplantation are limited to rodents, and there are no reports in primate animal models; therefore, it is difficult to evaluate the safety and effectiveness of the procedure for humans; 2) the mechanism of ESC proliferation and differentiation requires further study, and ESC differentiation are affected by local microenvironments, which might be significantly altered after spinal cord injury compared with the microenvironment of a normal body; therefore, directed differentiation is difficult to achieve; 3) there is a risk of forming teratomas after ESC implantation; and 4) there are ethical constraints [22].…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%